Analisis Pengaruh Sikap Toleransi Terhadap Hasil Belajar Siswa Fisika di Kelas XII IPA SMA Negeri 2 Kota Jambi - Nini Afrianty; Fauziah Yolviansyah (Journal Evaluation in Education (JEE), 2021)
Research objectives: This study aims to determine the effect of tolerance on physics learning outcomes for students of class XII science at SMA Negeri 2 Jambi City.Methodology: This research method is descriptive type, with a quantitative research approach. The samples studied were 20 students of class XII IPA 6, 20 respondents of class XII IPA 7, and 20 respondents of class XII IPA 8.Main findings: The results of this study based on hypothesis testing conducted using the correlation test, it was found that the student's tolerance attitude towards physics learning outcomes XII IPA at SMA Negeri 2 Jambi City has a very significant effect, meaning that there is a relationship between tolerance attitudes towards physics learning outcomesResearch novelty: This study reinforces previous research